Implementasi Location Based Service Dalam Perancangan Aplikasi Pencarian Lokasi Tambal Ban Di Kota Bengkulu - Dian Ariestanto; Dedy Abdullah; Muntahanah Muntahanah; Ardi Wijaya (Jurnal Media Infotama, 2025)
The LBS technology used in the tire patch location search application in Bengkulu City will help customers find the tire patch that best suits their preferences and location. With its ever-evolving environment, Bengkulu will also benefit from the adoption of this technology. By incorporating LBS technology in the design of tire patch locator applications, the city can encourage local trade, provide support to small and medium-sized entrepreneurs, and create a healthier and more sustainable business ecosystem. The purpose of this research is to find and develop innovative solutions to meet customer needs and support the growth of local businesses. This study examines the potential benefits of incorporating LBS technology in the application of finding tire patching locations in Bengkulu City. Data Collection: Some of the methods used to collect data to obtain the necessary information are literature studies; This method involves reviewing research books and journals relevant to the research subject to gain a better understanding of materials such as Location-based Services, Google Maps APIs, and location-based services. The menu features, which are required to build this app, include an app menu that consists of the location of the tire patch and information about the tire patch.